Implementasi Pengembangan Kurikulum Muhammadiyah Dalam Pembelajaran bahasa Arab di Sekolah Dasar - Fuadhi, Muhammad Iqbal; Thohir, Muhammad; Muttaqiyyah, Almar’atul; Sakinah, Nelly; Humaidah, Ulil Irzaqotul (STIQ Amuntai, 2025)
This research discusses the curriculum as a collection of learning materials designed systematically and customised based on all classroom activities and social relationships to achieve academic learning objectives. This type of research is qualitative with a literature study approach. The Al-Islam Muhammadiyah and Arabic curriculum is designed and formulated under the guidance of the Muhammadiyah Regional Leadership. The ISMUBA curriculum, which encompasses Islamic religious education and the Arabic language, is implemented in Muhammadiyah educational institutions. In implementing Arabic language learning, the curriculum is a step to improve foreign language skills, especially Arabic, for students. It includes several stages of learning to become skilled in speaking Arabic, classified into levels: beginner, intermediate, and advanced. For beginner-level Arabic learners, it is a first step to being able to facilitate foreign language speaking skills, encourage students to compose sentences neatly, and provide various enrichment to train students' speaking skills; for intermediate-level learners, honing Arabic language skills through live performances or demonstrations in the form of drama and encouraging active participation from students through discussion activities according to the theme. Finally, for Arabic learners at the advanced level, describing verbally what is understood according to the theme and the topic being reviewed connects with events that enter human life.